2013
DOI: 10.1542/peds.2013-0108
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Activity and Neurodevelopment in Boys and Girls

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Prenatal and postnatal organophosphate (cholinesterase inhibitor) pesticide exposure has been associated with delays in attention, memory, intelligence, and inhibitory control. Two recent studies reported decreased attention and working memory with greater exposure to organophosphates in boys but not in girls.WHAT THIS STUDY ADDS: This is the first study to report associations between decreased acetylcholinesterase activity, a stable marker of cholinesterase inhibitor pesticide ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
6
37
4
1
Order By: Relevance
“…The variation in impulsivity and depression levels may be caused by OPs exposure dose dependently; this could be established by studies on larger populations. In our study no significant association between low AChE activity and gender was found, but gender interaction was reported with OPs exposure in several studies [27,30,31]. Low AChE activity was related with deficits in neurodevelopment, particularly in attention, inhibition, and memory in boys but not in girls [27].…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The variation in impulsivity and depression levels may be caused by OPs exposure dose dependently; this could be established by studies on larger populations. In our study no significant association between low AChE activity and gender was found, but gender interaction was reported with OPs exposure in several studies [27,30,31]. Low AChE activity was related with deficits in neurodevelopment, particularly in attention, inhibition, and memory in boys but not in girls [27].…”
Section: Discussioncontrasting
confidence: 71%
“…In our study no significant association between low AChE activity and gender was found, but gender interaction was reported with OPs exposure in several studies [27,30,31]. Low AChE activity was related with deficits in neurodevelopment, particularly in attention, inhibition, and memory in boys but not in girls [27]. Prenatally organophosphate exposed children had greater decreases in attention among boys versus girls in agricultural areas in California [30] and in working memory among children in New York City [31].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Another study found that lower erythrocytic AChE activity in children ages 4–9 was associated with poorer neurodevelopment in boys, but not girls, particularly in attention, inhibition, and memory [100]. Neurodevelopment was measured using the NEPSY-II, an assessment that measures various developmental and NEuroPSYchological domains.…”
Section: Sex-specific Effects Of Childhood Op Exposurementioning
confidence: 99%
“…This study demonstrated a relationship between acute occupational poisoning with organophosphates and psychological distress, including suicidal thoughts. SUAREZ-LOPEZ et al (2013) found lower Acetylcholinesterase activity associated with lower performance on attention, inhibitory control, and memory in boys in Ecuador. These are critical cognitive skills that affect learning and academic performance.…”
Section: Rural Workers' Health and The Use Of Pesticides In Developinmentioning
confidence: 77%